A Domain Decomposition Method for Incompressible Viscous Flow - Strikwerda, John C; Scarbnick, Carl D (University of Wisconsin-Madison Department of Computer Sciences, 1989)
A method for using domain decomposition to solve the equations of incompressible viscous flow is presented. The method is described in detail, and test results are given for two test problems. A notable feature of the method is that the incompressibility constraint is never imposed. The domain decomposition uses finite difference and spectral methods on overlapping domains, with second-order accurate interpolation of the velocity relating the solutions on the different domains. The method is shown to be globally second-order accurate by the test results.